Towards the entrepreneurial university? Market-based reforms and institutional isomorphism in Colombia - Pineda, Pedro; Celis, Jorge (Education Policy Analysis Archives, 2017)
In this article, we analyze the new discourses on the university around two Colombian governmental programs: the student loan program Ser Pilo Paga and university rankings Mide. Although these programs can be labeled as market-based or neoliberal reforms, they have not been analyzed from a sociological perspective that discusses its relationship with changes in the idea itself of the university. We analyze the rhetoric surrounding its design and implementation through the content analysis of press articles and documents from governments and international organizations. From a neo-institutional perspective of world society theory, we find that loans have been mainly promoted by the World Bank, while rankings are directly copied from a global culture. There is also a rhetoric using the terms best, quality, excellence and technology that correspond with the global model of the entrepreneurial university. This idea contrasts, though, with terms such as equity, access, fairness and inclusion, in turn related to a discourse about social engagement that partially corresponds to the local idea of the Latin-American university. These tensions between university models where policy instruments are entangled should be further studied in other countries.